Value proposition to tourism coopetition : cases and tools - Chim-Miki, Adriana Fumi; Augusto da Costa, Rui (Emerald Publishing Limited, 2024)
This book contains an Open Access chapter. Discover the transformative power of 'coopetition' in the dynamic world of tourism and hospitality organisations, where inclusive development takes centre stage. The traditional model of competing alone is losing ground, making way for a new era of collaboration and partnership-driven competition. It is within this context that participating in a network becomes vital for organisations seeking a competitive advantage. Drawing on the work of a range of global contributors, the editors examine how this dyadic behaviour of simultaneously cooperating and competing among two or more players is transforming the tourism sector. Through meticulous planning and strategic implementation, 'coopetition' can generate remarkable advantages for tourism destinations and their stakeholders. Each chapter provides a real case of coopetition in the tourism sector and offers tools and ways to manage strategic networks under intentional coopetition. Value Proposition for Tourism Coopetition offers a wealth of insights and tools for stakeholders within the tourism industry, including operational takeaways and actionable strategies that will empower you to harness the full potential of coopetition in the tourism and hospitality sectors. Unlock the key to fostering sustainable growth, innovation, and collaborative success in an increasingly interconnected world.
Includes index.
Keywords: Tourism.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Hospitality and service industries.; Hospitality, sports, leisure and tourism industries.; elektronické knihy; electronic books